IMPLEMENTASI PERMENKUMHAM NO. 6 TAHUN 2013 TENTANG TATA TERTIB LAPAS KELAS 1 MAKASSAR PERSPEKTIF SIYASAH SYAR’IYYAH - Takdir, Muh. Supri; Darussalam (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This research the subject matter of how, the implementation of the Minister of Law and Human Rights Regulation No. 6 of 2013 concerning the Rules of the Class I Correctional Institution in Makassar from the siyasa syar'iyyah perspective. The objectives of this study are: To find out what violations occurred, the causal factors and how the Makassar Class 1 Penitentiary's efforts in carrying out the rules of conduct were viewed from the perspective of siyasah syar'iyyah. The main problems are: 1) What violations occurred in the implementation of the rules at the Makassar Class I Penitentiary?, 2) What factors caused the violation of the rules at the Makassar Class I Correctional Institution in terms of the Minister of Law and Human Rights Regulation No. 6 of 2013? and 3) What are the efforts of the Makassar Class 1 Penitentiary in implementing the rules of conduct from the perspective of Siyasah Syar'iyyah? This research is a field qualitative research using a syar'i normative approach and an empirical juridical approach. The results showed that: 1) Violations that occurred in the Makassar Class 1 Penitentiary in general were fights, the use of electronic devices such as cell phones and the use of sharp objects such as scissors, knives. 2) Factors causing the violation of the rules of conduct in Class 1 Makassar Prison, namely, inadequate facilities and infrastructure and lack of human resources (Lapas Officers). 3) The efforts implemented in the Makassar Class 1 Penitentiary, if correlated in the siyasah syar'iyyah concept, the researchers judged that they were in accordance with the concept of benefit/achievement of goals.